PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY ( TSTS ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 035 SEKELADI KECAMATAN TANAH PUTIH - Bakri, Bakri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPS grade IV SDN 035 Sekeladi Tanah Putih by the number of students sebanya 20 students. This study was conducted with two cycles, each cycle consisting of 2 meetings with 1 time daily tests. Instrument of data collection in this study is the observation sheet teacher, student observation sheet and achievement test. The results of the data analysis activities of teachers in the first cycle of the first meeting and the second meeting of the 65.63% increase to 68.75%. In the second cycle the first meeting and the second meeting 78.13% increase to 86.00%. Furthermore, the results of data analysis activities of students in the first cycle the first meeting and the second meeting 67.50% increase to 72.50%. In the second cycle the first meeting and the second meeting of the 77.50% increase to 84.00%. From the results of this study showed that student learning has increased average student learning outcomes in basic score is 69.75 increased in the first cycle to 79.50 increase again in the second cycle 80.75. To complete learn the basic score is 9 people (45%) increased in the first cycle to 17 people (85%) and increased again in the second cycle to 19 people (95%).It can be concluded that applied Model Cooperative Learning Two Stay Two Stray (TSTS) can improve learning outcomes IPS grade IV SDN 035 Sekeladi Tanah Putih.Key Words: Learning Model Two Stay Two Stray (TSTS), learning outcomes IPS